2017
DOI: 10.1021/acs.jpcc.7b01738
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Reduction Reaction in Highly Concentrated Electrolyte Solutions of Lithium Bis(trifluoromethanesulfonyl)amide/Dimethyl Sulfoxide

Abstract: The performance of current Li–air batteries is greatly limited by critical obstacles such as electrolyte decomposition, high charging overpotentials, and limited cycle life. Thus, much effort is devoted to fundamental studies to understand the mechanisms of discharge/charge processes and overcome the above-mentioned obstacles. In particular, the search for new stable electrolytes is vital for long-lasting and highly cyclable batteries. The highly reactive lithium superoxide intermediate (LiO2) produced during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
121
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(133 citation statements)
references
References 72 publications
12
121
0
Order By: Relevance
“…The decrease of the LiO 2 concentration would lead to a positive Nernstian shift of the potential of the ORR . Therefore this argumentation would also explain the observations of Tatara et al . There is a third explanation for this potential shift.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…The decrease of the LiO 2 concentration would lead to a positive Nernstian shift of the potential of the ORR . Therefore this argumentation would also explain the observations of Tatara et al . There is a third explanation for this potential shift.…”
Section: Resultsmentioning
confidence: 58%
“…Previously Tatara et al . investigated the effect of concentrated LiTFSI solution in DMSO on the ORR . With RRDE and Raman studies, the authors found that the amount of LiO 2 , as an ORR intermediate, is decreasing in higher concentrated solution.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows the recorded Raman spectra of fresh electrolytes in comparison to pure solvent. [25] 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 The concentrations of coordinated DMSO ([DMSO] coor ) molecules and uncoordinated or free DMSO ([DMSO] free ) molecules along with the coordination number (N DMSO ) in the electrolyte were estimated using Raman spectra (Table 1). A shift of CÀS symmetric and asymmetric stretching band towards high wavenumbers indicates much stronger CÀS bond of DMSO, suggesting an unusual coordination structure totally different from those in dilute solutions.…”
Section: Solution Propertiesmentioning
confidence: 99%
“…[22] TFSI À is moreover reported to form a stable SEI layer upon reduction on Li metal preventing further decomposition of solvent molecules. [25] Their work includes the finding of solvation structure of different concentrated electrolytes ranging from pure solvent up to 3.4 M using Raman spectroscopy. [25] Their work includes the finding of solvation structure of different concentrated electrolytes ranging from pure solvent up to 3.4 M using Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…The in solution structure of inorganic Li salts has been studied extensively in the field of lithium ion batteries. Raman spectroscopy is specifically useful for this purpose, and many researchers have proposed that lithium salts change their form from a solvent‐separated ion pair (SSIP) to a contacted ion pair (CIP) and an aggregate (AGG) species at higher concentrations (Figure ) . SSIP is also referred to as free species, whereas CIP and AGG are referred to as bound species (Figure ).…”
mentioning
confidence: 99%